Macrophomina phaseolina induced changes in plant water relations of resistant and susceptible cowpea genotypes - SATISH LODHA, UDAY BURMAN and (Indian Phytopathology, 2002)
Susceptibility of cowpea genotypes to dry root rot caused by M. phaseolina increased with increasing soil moisture stress. Water relation parameters of the healthy and diseased plants of cowpea genotypes were studied at the time of mild and severe moisture stress (20-40 d after sowing). Shoot water potential decreased significantly in the healthy and diseased plants of susceptible genotype ARS Durgapura compared with resistant V-265. At severe moisture stress, diseased plants of ARS Durgapura reflected greater magnitude of changes in leaf transpiration, turgiscence and temp. compared with those of V-265. Higher susceptibility of ARS Durgapura to Macrophomina infection was associated with impairment of its water uptake processes.